2018
DOI: 10.3390/ijms19103226
|View full text |Cite
|
Sign up to set email alerts
|

Novel Potentials of the DPP-4 Inhibitor Sitagliptin against Ischemia-Reperfusion (I/R) Injury in Rat Ex-Vivo Heart Model

Abstract: Dipeptidyl peptidase-4 (DPP-4) inhibitors are a class of oral anti-diabetic drugs, implicated in pleiotropic secondary cardioprotective effects. The aim of the study was to unveil the unknown and possible cardioprotective targets that can be exerted by sitagliptin (Sitg) against ischemia-reperfusion (I/R) injury. Male wistar rats received 2 weeks’ Sitg oral treatment of different doses (25, 50, 100, and 150 mg/kg/day), or saline as a Control. Hearts were then isolated and subjected to two different I/R injury … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 37 publications
1
28
1
Order By: Relevance
“…DPP-4 inhibitors increase the glucagon-like peptide 1 hormone (GLP-1) secretion, which successively stimulates the secretion of insulin and suppresses glucagon secretion. Emerging proof has proposed the neuroprotective effects of Sita (Al-Awar et al, 2018;Gupta, Singh, David, & Verma, 2013;Samuel et al, 2019). Number of reported literatures have demonstrated that Sita can increases the GLP-1 level in the brain along with improve the cognitive behaviors in rat model of AD (Civantos et al, 2017).…”
mentioning
confidence: 99%
“…DPP-4 inhibitors increase the glucagon-like peptide 1 hormone (GLP-1) secretion, which successively stimulates the secretion of insulin and suppresses glucagon secretion. Emerging proof has proposed the neuroprotective effects of Sita (Al-Awar et al, 2018;Gupta, Singh, David, & Verma, 2013;Samuel et al, 2019). Number of reported literatures have demonstrated that Sita can increases the GLP-1 level in the brain along with improve the cognitive behaviors in rat model of AD (Civantos et al, 2017).…”
mentioning
confidence: 99%
“…Moreover, no significant change was observed in serum Chol and TG levels in animal groups treated with Sitg (50 mg), compared to the controls. According to previous clinical studies, treatment with 50 mg dose of sitagliptin was effective in lowering lipid profile and glucose levels, and reducing DPP-4 activity by approximately 80% in patients with type 2 diabetes (Herman et al 2005;Shigematsu et al 2014) In the contrary of obtained findings from normolipidemic animals (Al-Awar et al 2018), the expected decrease in DPP-4 activity and increase in GLP-1 was not observed in high-fat diet condition. However, treatment with sitagliptin exhibited a significant decrease in DPP-4 protein level measured from heart tissues and aortas.…”
Section: Discussionmentioning
confidence: 91%
“…We hypothesized that hypercholesterolemia can be associated with increased infarct size, and sitagliptin can decrease its detrimental effect on the heart, clarifying mechanisms underlying this protection. Treatment with Sitg (50 mg) showed a significant decrease in infarct size and increase in cNOS activity in comparison with the control group, while this infarct size-limiting effect was abolished after NOS-inhibition by L-NAME, similarly as in normolipidemic animals (Al-Awar et al 2018). L-NAME is a non-selective NOS inhibitor that inhibits the 3 NOS isoforms: endothelial NOS (e-NOS), inducible NOS (i-NOS) and neuronal NOS (n-NOS).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations